An alternative approach for detecting hearing loss in adults with learning disabilities. (13th February 2021) - McShea, Lynzee; Giles, Karen; Murphy, Ashley; Ling, Jonathan
Accessible Summary: Annual health checks for people with learning disabilities should include a check of hearing. However, this hearing check only involves asking questions about hearing and does not include an actual hearing test. We tested the hearing of people with learning disabilities in the community. We found that some people had hearing problems that had not been picked up at their annual health check. We think the annual health check should be changed to include a hearing test. Abstract: Background: Annual health checks in primary care include hearing assessment, though current guidance recommends subjective assessment only. Previous studies suggest this is inadequate and recommend objective alternatives such as hearing screening. This study aimed to assess the feasibility of hearing screening and examine the last recorded annual health check outcome for hearing, for those diagnosed with hearing loss as a result of the screening process. Method: Hearing screening took place in four locations and 75 people with learning disabilities participated. Contact was made with each individual's GP to share results and to request onward referral where indicated. Findings: Wax occlusion prevented screening for 23%. Fifty‐seven people completed the screen, and 25 had suspected hearing loss. Of these, 22 people required referral to Audiology to verify their hearing thresholds. Only 13 were actually referred, and 11 individuals underwent assessment in Audiology, resulting in 10 being diagnosed with hearing loss. The most recent annual health check outcomes for hearing were examined for those diagnosed with hearing loss. Of the records we accessed, hearing loss had not been identified or actioned in every case. Conclusions: Hearing screening is shown here to be a suitable method for detecting hearing loss. We recommend changing current annual health check practice to incorporate objective screening. Only 12% of those with suspected hearing loss were known to Audiology services, suggesting a substantial proportion of undetected hearing loss in the community. We found evidence of apparent reluctance around referral and hearing aid fitting and make suggestions for improvement.